2013
DOI: 10.1002/jbm.a.34698
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the biocompatibility and stability of a gold nanoparticle collagen bioscaffold

Abstract: Collagen has been utilized as a scaffold for tissue engineering applications due to its many advantageous properties. However, collagen in its purified state is mechanically weak and prone to rapid degradation. To mitigate these effects, collagen can be crosslinked. Although enhanced mechanical properties and stability can be achieved by crosslinking, collagen can be rendered less biocompatible either due to changes in the overall microstructure or due to the cytotoxicity of the crosslinkers. We have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Similar to the effects of proliferation and migration, the concentration and size of the nanoparticle affects how the cells interact with the particles [39]. Previous studies of cellular ROS concentrations on collagen-100 nm AuNP constructs have shown a concentration dependent decrease in ROS production [16]. Too high of a concentration of nanoparticles may in- …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the effects of proliferation and migration, the concentration and size of the nanoparticle affects how the cells interact with the particles [39]. Previous studies of cellular ROS concentrations on collagen-100 nm AuNP constructs have shown a concentration dependent decrease in ROS production [16]. Too high of a concentration of nanoparticles may in- …”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the conjugation of AuNP to ECM tissue scaffolds enhances remodeling in vivo [15]. This remodeling influence can be attributed to an increase in cellularity and GAG production in the presence of AuNP [16]. AuNP can increase migration and adhesion of cells to tissue scaffolds due to AuNP' increased surface energy or due the creation of a topography favoring cell attachment [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such limitation is that the collagen scaffold degraded too quickly in vivo within the rabbit model, and almost no intact collagen scaffold could be found even after 4 weeks post-surgery. Advanced fabrication technology such as crosslinking with gold nanoparticles [28], could be utilized to slow down the collagen degradation rate. However, the biodegradation rate of the collagen matrix should also match the deposition of new tissues in situ.…”
Section: Discussionmentioning
confidence: 99%